สารประกอบเชิงซ้อนทองแดงของอนุพันธ์ควิโนลีนสำหรับเป็นตัวเร่งเชิงแสงในปฏิกิริยาการเติมแบบถ่ายโอนอะตอม - พิมพ์มาดา นาบำรุง (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
Atom transfer radical addition (ATRA) that involves carbon-carbon bond formation synthesis of organic compounds, especially for photocatalytic reactions. This project involved the design, synthesis and characterization of Q2P, an aminoquinoline derivative ligand for the Cu(II) ion to be used as a photocatalyst of the alkyl halide addition reaction on Indene and styrene. Ligand Q2P gave over 90% yield of the alkyl halide products resulted from the addition reaction. Then, the substitution reaction of the alkyl halide products formed by nucleophiles such as CH3OH, H2O and CH3CH2OH were studied. It was discovered that the substitution reaction was temperature-related but light-unrelated and the products were methyl ether, 2˚ alcohol and ethyl ether, respectively. In addition, two other aminoquinoline derivatives such as Q2M and QPM with substituent groups on the pyridine ring were synthesized. It was discovered that electron donor group on the pyridine ring had a negative impact on effectiveness of the catalytic activity of the Cu(II) complex in comparison with Q2P